BIK1 and ERECTA Play Opposing Roles in Both Leaf and Inflorescence Development in Arabidopsis - Chen, Sufen; Liu, Jun; Liu, Yu; Chen, Lijuan; Sun, Ting; Yao, Nan; Wang, Hong-Bin; Liu, Bing (Frontiers in Plant Science, 2019)
Plants employ cell-surface receptor-like kinases (RLKs) to detect extrinsic and intrinsic signals, thus make a trade-off between growth and immunity. The receptor-like cytoplasmic kinases (RLCKs) on the cytoplasmic side act as downstream components involved in the activation, transmission and integration of intracellular signals. In Arabidopsis thaliana，the RLCK BOTRYTIS-INDUCED KINASE1(BIK1) associates with multiple RLKs to regulate pathogen defense responses and brassinosteroid (BR) signaling. However, little is known about the biological functions of BIK1 in developmental processes in Arabidopsis. In this study, we established that mutation of ERECTA (ER), an important RLK, counteracts the developmental effects of loss of BIK1 function. BIK1 and ER play opposing roles in leaf morphogenesis and inflorescence architecture. Moreover, we confirmed that BIK1 is required to maintain appropriate auxin response during leaf margin morphogenesis. Finally, we found that BIK1 interacts with ER-family proteins and is directly phosphorylated by ER. Our findings might provide novel insight into the function of BIK1 in leaf and inflorescence development.